Spreader flaps for middle vault contour and stabilization - Kovacevic, Milos; Wurm, Jochen (Facial Plastic Surgery Clinics of North America, 2015)
Nasal hump excision is common during septorhinoplasty. Without appropriate restoration of the middle nasal vault, cosmetic and functional problems may ensue. Recently, spreader flaps have become an established alternative to traditional spreader grafts. Typical indications include primary rhinoplasty patients with hump noses, hump/tension noses, and moderately hooked or crooked noses. When suitable patients are selected, spreader flaps and their modifications represent a reliable alternative to the standard spreader graft, and when all of the necessary prerequisites are met, this technique obviates the need for additional cartilage grafting in most cases.
EVALuna2:19932